2022
DOI: 10.1038/s41598-022-18611-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tumor burden on survival in patients with recurrent or metastatic head and neck cancer treated with immune checkpoint inhibitors

Abstract: Immune checkpoint inhibitors (ICIs) have become the standard treatment for recurrent or metastatic head and neck cancer (RM-HNC). However, many patients fail to benefit from the treatment. Previous studies have revealed that tumor burden predicts the efficacy of ICIs, but this association remains unclear for RM-HNC. We retrospectively analyzed 94 patients with RM-HNC treated with ICI monotherapy. We estimated the tumor burden using the baseline number of metastatic lesions (BNML) and the baseline sum of the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Decision-making factors for selecting monotherapy or combination therapy include patient preference, biological age, tumor burden, speed of disease progression, and PD-L1 expression status [15]. PD-L1 expression and tumor burden, including the sum of the longest diameters of the target lesions and the number of metastatic lesions, are associated with prognosis in patients treated with ICIs [16,17]. In our cohort, treatment selection was based on these factors, and patients with higher CPS scores, smaller tumor volumes, and fewer metastatic lesions tended to be treated with pembrolizumab monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Decision-making factors for selecting monotherapy or combination therapy include patient preference, biological age, tumor burden, speed of disease progression, and PD-L1 expression status [15]. PD-L1 expression and tumor burden, including the sum of the longest diameters of the target lesions and the number of metastatic lesions, are associated with prognosis in patients treated with ICIs [16,17]. In our cohort, treatment selection was based on these factors, and patients with higher CPS scores, smaller tumor volumes, and fewer metastatic lesions tended to be treated with pembrolizumab monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor burden simply indicates the total amount of tumor in the body. Accumulating studies have demonstrated that tumor burden is an independent prognostic factor with a negative impact on survival in several types of malignancies, including melanoma [14], lung cancer [15][16][17][18], head and neck cancer [19,20], thyroid cancer [21] and lymphoma [22]. Kim et al conducted a systematic review and identified the negative impact of tumor burden on baseline immunity and treatment-induced immune responses [7].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these reasons, Gr and SumTLs are not widely used in clinical practice. Matoba et al also conducted another retrospective analysis of 94 patients with R/M HNSCC treated with immunotherapy [20]. They estimated the tumor burden using the number of tumor lesions and the size of the largest tumor lesions.…”
Section: Discussionmentioning
confidence: 99%